Effectiveness of Risk Management Strategies For Protecting Front-Line Workers From The Devastating Impact Of Covid-19 Pandemic With Major Focus on Their Mental Health Conditions (Indian Journal of Applied-Basic Medical Sciences, 2021)
Going to work during the COVID-19 pandemic has placed frontline workers under immense  and unprecedented pressures, putting their physical, mental, and social well-being at risk. Staff  under excessive or prolonged stress become more prone to frequent absences from work or  reduced productivity while at work, accidents, and mistakes. In the COVID-19 pandemic, this  may mean compromised quality and safety of care, breach of protocols and guidelines,  increased risk of infections, and compromised capacity of the health system and emergency  response teams to fight the pandemic. While frontline workers have the responsibility of caring  for themselves and verbalizing their needs and concerns, many of the efforts to prevent and  reduce stress and care for the mental health of frontline workers must be made by organizations,  managers, and health administrators.
Keywords: Frontline workers; COVID-19; mental health